Evaluating a decision tool for diagnosing diastolic dysfunction and estimation of left ventricular filling pressures in the presence of mitral annular calcium. Issue 11 (6th October 2020) - Haines, Philip G.; Dickey, John B.; Chambers, Alison B.; Ogunsua, Adedotun; Wu, Wen‐Chih; Aurigemma, Gerard P.
Abstract: Objectives: This study sought to evaluate a decision algorithm for the estimation of left ventricular filling pressure (LVFP) in patients with mitral annular calcification (MAC). Background: In a single center study, Abudiab et al evaluated echocardiographic parameters to estimate LVFP in patients with MAC against invasive hemodynamic measurements and developed a decision algorithm which demonstrated high predictive accuracy. Methods: Retrospectively, 55 patients (mean age 68.5 ± 11.5) with MAC and a left heart catheterization within 24 hours of an echocardiogram were identified. The decision algorithm was applied using echo data to classify patients as having normal or elevated LVFP which was then compared with the invasively obtained LVFP. Results: The algorithm performed poorly at predicting pre‐A LVFP as normal or high ( P  = .182). Accuracy for the algorithm was 0.59 [0.46, 0.72] (mean [95% CI]), sensitivity was 0.45 [0.28, 0.62], specificity was 0.73 [0.54, 0.86], false positive rate was 0.27 [0.14, 0.46], and false negative rate was 0.55 [0.38, 0.72]. E/A ratio, IVRT, and E/e'ratio showed no significant relationship to actual patient LVFP. Conclusions: The Abudiab et al algorithm failed to demonstrate comparable sensitivity, specificity, and accuracy in our sample. Additional study is necessary to refine this tool prior to more widespread use in clinical practice.